Peranan pengurusan sekolah dalam meningkatkan kepuasan kerja guru di daerah Kota Tinggi - Abdullah, Azhari (2013)
The purpose of this study was to identify the administrator roles in increasing job satisfaction among the teachers in the district of Kota Tinggi. The study involved a sample of 286 teachers in five secondary schools in the district of Kota Tinggi. The data were collected through questionnaires and interviews. Qualitative interviews were conducted with four teachers and all the interviewers, opinions were recorded by researcher. The quantitative data were analyzed by using Statistical Package for Social Sciences (SPSS) version16.0. Meanwhile the qualitative data were analysed using thematic process. Analysis of the data found that teacher’s job satisfaction at was moderate level (mean 3.61) and the management had helped to increase the job satisfaction seriously (mean 4.08). In addition, the cause of medium level satisfaction among teachers were identified. Furthermore, the role played by management in improving job satisfaction had also been presented in this study.